Fluconazole‐resistant Candida parapsilosis strains with a Y132F substitution in the ERG11 gene causing invasive infections in a neonatal unit, South Africa. Issue 5 (13th April 2020) - Magobo, Rindidzani E.; Lockhart, Shawn R.; Govender, Nelesh P.
Summary: Introduction: The prevalence of azole resistance in C parapsilosis is very low in most parts of the world. However, South Africa has reported an exceptionally high prevalence of azole resistance in C parapsilosis strains isolated from candidaemia cases. We aimed to determine the possible molecular mechanisms of fluconazole resistance in C parapsilosis isolates obtained through surveillance at a large neonatal unit at a South African academic hospital. Methods: We sequenced the ERG11 and MRR1 genes of C parapsilosis isolates recovered from cases of neonatal candidemia, followed by microsatellite genotyping. A total of 73 isolates with antifungal susceptibility results were analysed. Results: Of these, 57 (78%) were resistant, 11 (15%) susceptible dose‐dependent and 5 (7%) susceptible. The most commonly identified amino acid substitution within the ERG11 gene was Y132F in 68% (39/57) of fluconazole‐resistant isolates and none in susceptible isolates. Three amino acid substitutions (R405K, G583R and A619V) and 1 nucleotide deletion at position 1331 were identified within MRR1 gene in 19 (26%) isolates. Microsatellite genotyping grouped isolates into four clusters (50 isolates). Cluster 1 accounted for 23% (17/73) of all cases, cluster 2 for 22% (16/73), cluster 3 for 14% (10/73) and cluster 4 for 10% (7/73). We found an association between cluster type and fluconazole resistance ( P ‐value = .004). Isolates harbouring the Y132F substitution were more likely to belong to a cluster than non‐Y132F isolates. Conclusion: Fluconazole resistance in C parapsilosis strains from a single South African neonatal unit was associated with cluster type and predominantly driven by Y123F amino acid substitutions in the ERG11 gene.